2013
DOI: 10.1109/tuffc.2013.2550
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance ultrasonic system for the simultaneous transmission of data and power through solid metal barriers

Abstract: This paper presents a system capable of simultaneous high-power and high-data-rate transmission through solid metal barriers using ultrasound. By coaxially aligning a pair of piezoelectric transducers on opposite sides of a metal wall and acoustically coupling them to the barrier, an acoustic- electric transmission channel is formed which prevents the need for physical penetration. Independent data and power channels are utilized, but they are only separated by 25.4 mm to reduce the system's form factor. Comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 17 publications
1
60
0
1
Order By: Relevance
“…The LOS channel impulse response is convolution of the three system impulse response [9]. (ICMEMTC 2016) Transducer model.…”
Section: Fig 1 the Model Of Ultrasonic Communication Systemmentioning
confidence: 99%
“…The LOS channel impulse response is convolution of the three system impulse response [9]. (ICMEMTC 2016) Transducer model.…”
Section: Fig 1 the Model Of Ultrasonic Communication Systemmentioning
confidence: 99%
“…Lawry et al, presented a UTMWPT system with a CF-DFBR as an AC-DC converter [17,18]. The transducers operated at about 1 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 also shows that the quality factor (Q) values of the transducers are smaller than unit at the resonant frequencies. The low Q values make the system high-loss but reduce the resonant frequency consistency requirements on the TX and RX transducers [17].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has shown that echoing of acoustic energy within the channel leads to significant inter-symbol interference when transmitting at a high data rate [3]. An echo cancelation technique was developed that uses a predistortion filter at the transmitting to cause destructive interference and partial cancelation of echoes at the receiver [4][5][6].…”
Section: Introductionmentioning
confidence: 99%